2017
DOI: 10.1080/19396368.2017.1406013
|View full text |Cite
|
Sign up to set email alerts
|

Initial germ cell to somatic cell ratio impacts the efficiency of SSC expansion in vitro

Abstract: SSC: spermatogonial stem cells; DP: differential plating; NOA: non-obstructive azoospermia; MACS: magnetic-activated cells sorting; FACS: fluorescence-activated cells sorting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Enrichment of cell suspensions in SSCs is also possible using several methods, such as cell sorting followed by in vitro expansion [ 111 ] or differential plating [ 112 ]. However, these techniques still need to be refined because of partial results in terms of cell purity [ 113 ] and viability.…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment of cell suspensions in SSCs is also possible using several methods, such as cell sorting followed by in vitro expansion [ 111 ] or differential plating [ 112 ]. However, these techniques still need to be refined because of partial results in terms of cell purity [ 113 ] and viability.…”
Section: Resultsmentioning
confidence: 99%
“…The percentages of PLZF, ITGA6, and GFRα1 positive cells in the SSCs cultured for 7 days with different doses of growth factors namely, epidermal growth factor at 10 (E10), 15 (E15), and 20 (E20) ng/ml; glial cell line-derived neurotrophic growth factor at 40 (G40), 70 (G70), and 100 (G100) ng/ml and insulinlike growth factor-1 at 50 (I50), 100 (I100), and 150 (I150) ng/ml. n Values did not differ significantly between the control and the treatment groups were carried out successfully with various levels of purified SSCs, 26% [39] and 91% [11] in rodents, 70-73% [40,41] in porcine, 72% in bovine [42], and 83% in goat [43]. The variation in the purity of the SSC obtained in the present study as compared to previous studies may be attributed to the developmental stage of the testes used for isolation, differences in enrichment protocol (single or double) employed and markers used for validation [13].…”
Section: Discussionmentioning
confidence: 99%
“…35,47 Indeed, the importance of the germ-versus somatic-cell ratio in culture was demonstrated, showing an impact on SSC proliferation. 52,53 The influence of the medium was also pinpointed when Gat et al observed more germ-cell aggregate formation when using DMEM/ F12 instead of StemPro-34. 54 Others also examined the efficiency of differential plating to select germ cells from TCSs, but did not find a difference in germ-cell numbers recovered from whole TCSs and differentially plated cells after 14 days of culture.…”
Section: Ssc Propagationmentioning
confidence: 99%